2021
DOI: 10.1080/02687038.2021.1970099
|View full text |Cite
|
Sign up to set email alerts
|

Language processing in glioma patients: speed or accuracy as a sensitive measure?

Abstract: Background: Glioma (brain tumour) patients can suffer from mild linguistic and non-linguistic cognitive problems when the glioma is localised in an eloquent brain area. Word-finding problems are among the most frequently reported complaints. However, mild problems are difficult to measure with standard language tests because they are generally designed for more severe aphasic patients. Aims:The aim of the present study was to investigate whether word-finding problems reported by patients with a glioma can be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
3
1
Order By: Relevance
“…Second, tumor in the right hemisphere was more often observed in the musical group which could be a confounding on language performance, considering that language is often lateralized in the left hemisphere. However, we argue that this does not influence our results as prior research found that hemispheric lateralization does not affect language performance on the DIMA scale in glioma patients (Mooijman et al, 2021;Satoer et al, 2022).…”
Section: Strengths and Limitationscontrasting
confidence: 45%
“…Second, tumor in the right hemisphere was more often observed in the musical group which could be a confounding on language performance, considering that language is often lateralized in the left hemisphere. However, we argue that this does not influence our results as prior research found that hemispheric lateralization does not affect language performance on the DIMA scale in glioma patients (Mooijman et al, 2021;Satoer et al, 2022).…”
Section: Strengths and Limitationscontrasting
confidence: 45%
“…In recent years, the language abilities of people with brain tumours have received much attention (Mooijman et al, 2021; Rofes, Mandonnet, et al, 2017; Satoer et al, 2013). Tasks and assessments at the sentence and at the word level have been employed.…”
Section: Introductionmentioning
confidence: 99%
“…Satoer et al (2013) reported that during preoperative spontaneous speech individuals with brain tumours produced more incomplete sentences and had shorter mean length of utterance than a matched control group. However, even though people with brain tumours report word finding problems, single‐word object naming tasks are not always sensitive enough to detect any preoperative difficulties (Mooijman et al, 2021). More importantly, the numbers of patients that are classified as ‘impaired’ seem to differ according to the linguistic modality and the linguistic stimuli used in each neurosurgical centre.…”
Section: Introductionmentioning
confidence: 99%
“…However, the outcomes can assist selection of variables in future studies. Language domains that appear most promising in relation to FC networks are word retrieval (as assessed with object naming), grammar, and comprehension of visual input when using a sufficiently sensitive test (e.g., combination of accuracy and speed, Mooijman et al, 2021 ) and to a lesser extent semantics and writing. FC network characteristics that appear most promising in relation to language functioning are MST degree, eccentricity and diameter in the theta band, and weighted small-world index in the alpha band.…”
Section: Discussionmentioning
confidence: 99%